Language Change And Word Creation Processes In Social Networks - Komilova, Zulhumor; Jo`rayeva, Mohlaroyim (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This work examines the hidden and overt influence of social networks on language development. New words, abbreviations, compound words, and expressions created on the basis of memes that appear in virtual communication are gaining a strong place not only in online conversations, but also in everyday oral speech. The study shows that social networks not only influence language, but also actively shape it, and the language habits of the new generation are further accelerating this process. The variability, adaptability, and ability of language to absorb new layers of meaning are analyzed as the main features of this process.